Perancangan Identitas Visual Dan Branding UMKM Di Desa Penanggungan - Navaldy Arya Pratama; Pungky Febi Arifianto (Lembaga Pengembangan Kinerja Dosen, 2024)
Bina Desa is a form of community service carried out by students by plunging directly into the community environment so that students learn to socialize and know the problems faced in the environment, the PKKM Bina Desa Program is expected to be a learning medium for students and the problems faced by the community can be helped and get solutions from the knowledge applied by students. PKKM Bina Desa Tawas 2023, which is located in Penanggungan Village, Trawas District, Mojokerto Regency, has been running a work program for 3 months from August 21 - November 24, 2023, One of the work programs that I worked on was a visual identity design and branding program for Penanggungan village MSMEs, The problem experienced by owners and managers of MSMEs in Penanggungan village is the lack of education about the importance of visual identity and branding in their snack products, so that they have not been able to reach markets outside their regional area. Therefore, this visual identity and branding design program is sought to help MSMEs so that they can be better able to develop their products in a more organized manner and can reach a larger market in the future. This program has been completed on time and pursued as best as possible.